The effects of the COVID-19 pandemic on the diagnosis and prognosis of melanoma 2 years after the pandemic in two Romanian counties - Apostu, Adina Patricia; Vesa, Ștefan Cristian; Frățilă, Simona; Iancu, Gabriela; Bejinariu, Nona; Muntean, Maximilian; Șenilă, Simona C.; Baba, Oana Alexandra; Secășan, Cristina Pop; Ungureanu, Loredana (Frontiers in Medicine, 2024)
Background The COVID-19 pandemic disrupted the healthcare system and negatively affected the diagnosis and management of melanoma worldwide. The purpose of this study is to investigate the long-term effects of the COVID-19 pandemic on the diagnosis and prognosis of melanoma. Materials and methods This retrospective cohort study included histopathologically confirmed melanoma cases from March 2019 to February 2023 in Cluj and Bihor counties. Data from the post-COVID-19 period (March 2021 to February 2023) were compared to the pre-COVID-19 period (March 2019 to February 2020) and the COVID-19 period (March 2020 to February 2021). Patient characteristics, monthly diagnostics, histological subtypes, and key histological features were analyzed using statistical tests. Results The number of melanoma cases diagnosed annually decreased by 31.37 and 23.75% in the first and second post-pandemic years, respectively, compared to pre-pandemic numbers. Diagnostic rates also decreased by 14.9 and 5.4% in the first and second post-pandemic years, respectively, compared to the pandemic period. Prognostic factors worsened in the post-pandemic period, with higher Breslow index and mitotic rate, and increased ulceration and thick melanomas compared to the pre-pandemic period. Conclusion The COVID-19 pandemic had a long-lasting impact on the diagnosis of melanoma in Romania, resulting in advanced stages and unfavorable prognostic factors. Larger global studies are needed to comprehensively understand the pandemic’s long-term effects on the diagnosis of melanoma.